واقع استخدام تكنولوجيا الاتصال الحديثة في قطاع السياحة - نيبوع, نبيل (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة المعنونة ب" واقع استخدام تكنولوجيا الاتصال الحديثة بقطاع السياحة " الى الاجابة عن التساؤل الرئيسي المتمثل في ماهو واقع استخدام تكنولوجيا الاتصال الحديثة بمديرية السياحة والصناعة التقليدية لولاية توقرت للإجابة على هذا السؤال اعتمد الباحث على التساؤلين الهامين - 1 ما مدى استخدام تكنولوجيا الاتصال الحديثة )جهاز الحاسوب، شبكة الإنترنت الهاتف الذكي( في مديرية السياحة والصناعة التقليدية - 2 ماهي معوقات استخدام تكنولوجيا الاتصال الحديثة )جهاز الحاسوب، شبكة الإنترنت الهاتف الذكي( في مديرية السياحة والصناعة التقليدية والتي تندرج تحتها فرضيتين: - يوجد تباين في استخدام تكنولوجيا الاتصال الحديثة بمديرية السياحة والصناعة التقليدية - توجد معيقات تنظيمية وشخصية في استخدام تكنولوجيا الاتصال الحديثة بمديرية السياحة والصناعة التقليدية حيث تم الاعتماد على الاجراءات المنهجية المتمثلة في المدخل المنهجي لنظرية انتشار المبتكرات والمنهج الوصفي التحليلي لتحليلي وهذا باستخدام مجموعة من الأدوات لجمع البيانات انطلاقا من الملاحظة البسيطة مرورا بالمقابلة، واستمارة الاستبيان وصولا الى الأساليب لتحليل البيانات. وطبقت هده الأدوات على مجتمع البحث المتمثل في موظفي مديرية السياحة والصناعة التقليدية حيث كان عددهم 28 موظفا تم اختيارهم على طريقة المسح الشامل واسترجعت 23 استمارة من أصل 28 وأسفرت نتائج الدراسة الميدانية: - ان استخدام جهاز الحاسوب عامل أساسي في اختصار الوقت والجهد وتحسين اداء العمل كما يساهم في حفظ المعلومات والبيانات مما يدعوا الى فتح مجالات التكوين - عدم توفر جهاز الحاسوب بالشكل الكافي وعدم اتصالها لشبكة الانترنت - كشفت الدراسة أن جل الموظفين يملكون هاتفا ذكي يستخدمونه خلال العمل حيث تباينت استخداماته - عدم الالمام بتطبيقات الهاتف الذكي المتنوعة في مختلف المجالات العمل الاداري - الانترنت تستخدم بدرجة كبيرة في الانجاز الأعمال المتمثلة في المراسلات والإشهار كما أن بعض الموظفين يستخدمونها في الترفيه والتواصل مع الاصدقاء - ضعف مستويات اللغات الأجنبية عند الموظفين مما يعيق عمليات التحكم الجيدة في استخدام بتكنولوجيا الاتصال الحديثة ومواكبة التقنيات الحديثة _ تم التوصل الى أن وسائل تكنولوجيا الاتصال الحديثة معرضة لاختراق البيانات مما يتحفظ الموظفون في استخدامها . The study under investigation entitled “ The reality of using modern communication technology in the tourism sector" aims to answer the following main question “what is the reality of the use of modern communication technology in the Directorate of Tourism and Handicrafts in Touggourt wilaya .To answer this question .The researcher raised the following questions . 1. To what extent is the use of modern communication technology (computer, Internet and smartphone) in the Directorate of Tourism and Handicrafts ? 2)What are the obstacles in using the modern communication technology (computer, Internet and smartphone) in the Directorate of Tourism and Handicrafts ? In light of the previous research questions. We put forward the following hypothesis: - There is a discrepancy in the use of modern communication technology in the Directorate of Tourism and Handicrafts - There are organizational and personal obstacles in the use of modern communication technology in the Directorate of Tourism and Handicrafts . In order to achieve the stated aims of the present study, a methodological procedures represented in the methodological approach to the theory of the spread of innovations and the descriptive analytical approach to my analysis were relied upon using a set of tools to collect data from simple observation through the interview, the questionnaire form to the methods of data analysis.The questionnaire was administered to 28 employees who were selected on the comprehensive survey method, and 23 out of 28 forms were retrieved .The results obtained revealed that the use of the computer is a key factor in reducing time and effort and improving work performance as well as contributing to the preservation of information and data, which calls for opening areas of training. - Insufficient computer availability and lack of Internet connection - The study revealed that most employees have a smartphone that they use during work, as its uses varied - The Internet is widely used in the achievement of the work of correspondence and advertisement , and some employees use it in entertainment and communication with friends. - Poor levels of foreign languages among employees, which hinders good control processes in the use of modern communication technology and keeping pace with modern technologies. It was concluded that the means of modern communication technology are subjected to data breaches, which employees are reticent to use.
دراسة مسحية مديرية السياحة والصناعة التقليدية بتوقرت
مذكرة ماسترعلم اجتماع